Managing obstetric bleeding in Wales: A qualitative evaluation of the OBS Cymru care bundle using Normalisation Process Theory - Tanvi Rai; Lisa E. Hinton; Rosa Mackay; Mairead Black; Julia Sanders; Pauline Slade; Amy Elsmore; Amrit Dhadda; William Parry-Smith; Rachel Collis; Stavros Petrou; Simon Stanworth; et al. (PLoS ONE, 2025)
Background Post-partum haemorrhage (PPH) is one of the leading causes of maternal mortality and morbidity worldwide. The Obstetric Bleeding Strategy (OBS) care bundle for PPH management was adopted into Welsh national guidelines in 2019 (as OBS Cymru), and is currently being implemented across 36 sites in the rest of the UK through the OBS UK stepped-wedge cluster randomised controlled trial. We conducted a qualitative evaluation of the OBS care bundle five years after its adoption to inform plans for optimising its implementation across the UK. Methods We conducted ethnographic observations, informal conversations and qualitative interviews with multidisciplinary teams (MDT) in four maternity units in Wales. Data were analysed thematically and using Normalisation Process Theory. Results The OBS Cymru protocol was used daily and MDT members believe it improves the quality and safety of PPH management. The paper proforma supporting OBS Cymru was the ‘boundary object’ that kept the care bundle in view while clarifying individualised roles across the MDT during a PPH and prompting improved and continuous communication as bleeding progressed. The standardisation of processes through the care bundle was seen as enabling all staff with an overall knowledge of PPH care, while situating the prominence of their particular roles within a greater whole. Enacting the bundle in practice varied slightly across different settings, according to staffing structures (e.g., in delivery rooms versus theatre births) and caseload, and some residual tensions remained regarding expectations from different staff members and levels of support provided regarding OBS Cymru. Conclusions Despite some small-scale variations, OBS care bundle has become normalised as standard PPH care in Wales. Insights from this evaluation, such as the centrality of the proforma in holding the bundle together, and need for greater clarity in staff role expectations, have informed implementation plans for the OBS UK trial.